The Antioxidant Activity of Ethanol Extract of Chinese Betel Leaf (Peperomia pellucida) using the DPPH Method with Potential as an Antidiabetic Agent - Sadik, Fahmi; Anwar, Mahgial; Nasir, Muh (Universitas Nusa Cendana, 2025)
Complications of diabetes mellitus are known to be exacerbated by oxidative stress. The Chinese pepper plant (Peperomia pellucida), known as a source of natural antioxidants, was studied for its potential in this research. We evaluated the in vitro antioxidant capacity of the ethanol extract of P. pellucida leaves using the DPPH method to see its relationship with antidiabetic potential. The process involves extracting the leaves using ethanol, followed by testing the extract's ability to scavenge DPPH free radicals at various concentration levels to determine the IC50 value. It was found that the ethanol extract showed antioxidant activity with an IC50 of 65.813 ppm, indicating its effectiveness as a free radical scavenger. This study concludes that the ethanol extract of Chinese betel leaves has strong in vitro antioxidant activity based on the DPPH test. These results support the further development of this extract as an adjunct therapy for diabetes mellitus, primarily in reducing oxidative stress. Follow-up suggestions include testing more specific antidiabetic mechanisms (such as α-amylase/α-glucosidase inhibition and in vivo studies), fractionation to isolate active compounds, and toxicity evaluation for development safety.